KEARIFAN LOKAL PETANI DALAM USAHATANI TANAMAN JAGUNG DI DESA BENTE KECAMATAN KABAWO KABUPATEN MUNA - Narsin, Narsin; Batoa, Hartina; Hamzah, Awaluddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This research aims to investigate the forms of local wisdom among farmers involved in the cultivation process of corn farming in Bente Village. The study was conducted in Bente Village, Kabawo Subdistrict, Muna Regency, with a total of 5 informants. Interview guidelines were used as a means of data collection, along with interview techniques and documentation. The data analysis method employed was qualitative descriptive analysis. The results of the research indicate that the forms of local wisdom among farmers in corn farming in Bente Village manifest in both tangible and textual forms, including the procedures and value systems, as well as intangible forms such as prayers and mantras. The local wisdom of farmers in the stages of corn farming in Bente Village includes land clearing (detambori), tree cutting (detughori), burning (desula), fencing (deghala), kaago-ago, seed preparation (dewine), planting (detisa), maintenance (derawati), corn harvesting (depasele), young corn rituals (desopori), main harvest (detongka), and post-harvest (detoto).